(untitled) (Fiep Bulletin - online, 2011)
Alcoholism became a public health problem in developed countries, and today it is the third death cause, losing only for cancer and heart diseases. Today around two billion people in the world, use liquor. Alcohol has brought serious social consequences like: high level of interpersonal violence, homicides, risk sexual behavior, not constant use of condoms with consequent incidence of DST/AIDS and the increase of accidents with motor vehicles resulting in the loss of lives. To survey the consumption of alcohol and its consequences among the military police officers a questionnaire created by the World Health Organization technicians was applied – AUDIT (Alcohol Use Disorders Identifications Test)in 263 police officers in a contingent of 408, representing 64,4% of the officers who work in the 5th Military Police Battalion in Londrina-Parana. The results of the research show that 83,65% are in the low consumption scale, 8,74% in the risk use scale,2,28% are in the harmful use and 5,32% with possible addiction. The research shows that the liquor consumption has led 12% of the police officers to be unable to perform their jobs properly in his role of security agent, family and community member. The data allow to reflect on the alcohol problem in the 5th Battalion as well as in other garrisons in Parana State.